Alovsat, Quliyev - (:unkn) unknown (My University, 2026)
Alovsat Shura oglu Guliyev has more than 40 years of professional experience in geodesy, photogrammetry, remote sensing, cartography, and space geodesy. He studied at Baku Polytechnic College and graduated from the Novosibirsk Institute of Engineers of Geodesy, Aerial Photography and Cartography in 1992 with a degree in Photogrammetry. He began his professional career in 1992 in the Ganja Topogeodetic Expedition and subsequently held engineering and managerial positions in aerogeodesy, geodesy, and cadastral organizations. From 2007 to 2024, he worked at the State Oil Company of the Republic of Azerbaijan (SOCAR), including as a Senior Geodesist. In 2002, he completed professional training in Digital Photogrammetry and Mapping at PASCO in Tokyo, Japan. From 2018 to 2024, he conducted scientific research at Siberian State University of Geosystems and Technologies in Russia. In 2025, he was awarded the degree of Candidate of Technical Sciences in Space Research and Photogrammetry. Since 2025, he has been working as a Senior Lecturer at the Department of Geomatics, Faculty of Transport, at the Azerbaijan University of Architecture and Construction (AzUAC). He teaches Photogrammetry, Remote Sensing, Digital Image Processing, Geodesy, Engineering Geodesy, and Surveying. Alovsat Guliyev is the author of more than 15 scientific publications. His research interests include the integration and analysis of regional aerospace data, photogrammetry, remote sensing, and geospatial technologies.